Quantitative Dot Blot Assays to determine Vibrio cholerae O1 Lipopolysaccharide concentration using Monoclonal Antibody - Aznar EG; Alfaro OO; Cuello DC; Blanco OC; Sánchez AF; et al (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2017)
Introduction: Rapid diagnosis is fundamental for epidemiological control of Cholera disease. Contradictorily the gold standard test (stool culture) takes several days. Finlay Vaccine Institute obtained an Immunoagglutination test for rapid diagnosis of Cholera (FCIT), based on a monoclonal antibody anti- LPS O1 coupled to latex particles. FCIT,includes a positive control (LPS O1 Ogawa), which quantification is mandatory to obtain the registration of the test.The objective of the work was to develop a quantitative Dot Blot to determine the LPS O1 concentration in FCIT Positive control, using a peroxidase-conjugated mAb. Materials and Methods: Conjugation of mAb anti LPS O1 to peroxidase enzyme was carry out by periodate method. Quantitation of LPS O1 was accomplish by quantity Dot Blot. For capture Vibrio cholerae 569B Lipopolysaccharides from Sigma, was used as standard of the curve (40 μg/mL to 0.6 μg/mL) and fi ve lots of FCIT positive control were applied as sample. For detection conjugated mAb-HRP was employed at dilution 1:5000. The development of the reaction was carried out using SIGMAFAST™ DAB Tablet. The images were captured using the GS-800 densitometer and the spots density (Int/mm2) were calculated using the ImageJ software. The LPS concentration in positive control lots was calculated employed Ascent Software. Results: The mAb was conjugated to the HRP effi ciently with working dilutions range from 1:2500 to 1:10,000. A four-parameter fi t model curve was obtained with R2 of 0.99. Of the fi ve FCIT positive control lots evaluated, four complied with 30% of the expected concentration, for an 80% effectiveness of the technique. Conclusions: These results suggest that the quantitative Dot Blot using the mAbC anti Vibrio cholerae LPS O1, can be employed for the quantifi cation of LPS in batches of the FCIT positive control, from the purifi cation and production stages, as well as for the stability evaluation.